2015
DOI: 10.1074/jbc.m115.646422
|View full text |Cite
|
Sign up to set email alerts
|

The Us3 Protein of Herpes Simplex Virus 1 Inhibits T Cell Signaling by Confining Linker for Activation of T Cells (LAT) Activation via TRAF6 Protein

Abstract: Background: HSV-1 inhibits T cell functions, but the underlying mechanism is unclear. Results: The HSV-1 Us3 protein disrupts T cell signal transduction by inhibiting the ubiquitination of LAT. Conclusion: The Us3 protein is a crucial factor to suppress T cell activation in HSV-1 infection. Significance: Inhibition of T cell immunity may promote HSV-1 replication or persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…A similar effect was observed with other HSV glycoproteins, namely, gB, gH, gI, and gL in the same study [208]. A recent report suggests that impaired T-cell activation would also be mediated by HSV U s 3 protein interference with T-cell receptor signaling, specifically by altering linker for activation of T cells (LAT1) within these cells [209]. Importantly, infection of T cells (other than Jurkat cells) requires the presence of antigen-presenting cells for efficient virus transfer, a process termed virological synapse.…”
Section: Evasion Of T Cell Immunitysupporting
confidence: 78%
“…A similar effect was observed with other HSV glycoproteins, namely, gB, gH, gI, and gL in the same study [208]. A recent report suggests that impaired T-cell activation would also be mediated by HSV U s 3 protein interference with T-cell receptor signaling, specifically by altering linker for activation of T cells (LAT1) within these cells [209]. Importantly, infection of T cells (other than Jurkat cells) requires the presence of antigen-presenting cells for efficient virus transfer, a process termed virological synapse.…”
Section: Evasion Of T Cell Immunitysupporting
confidence: 78%
“…Because of defects in those pathways in cancer cells, mutations in many of these genes endow oncolytic activity to HSV [3]. Type 1 IFN production and its signaling pathway is key to antiviral innate immunity and thus HSV targets multiple steps in the pathway: (i) TLR signaling pathway; TLR3 and TLR2 signaling to TRAF6 are inhibited by Us3 [53], TRAF3 is inhibited by UL36 deubiquitinase [15], MyD88 and NF-kB subunits P50 and P65 are inhibited by ICP0 [54], nuclear translocation of NF-kB is inhibited by UL42 and Us3 [55,56], and ICP27 blocks NF-kB by binding to IkBα [57]. (ii) RIG-I-like receptor (RLR) signaling pathway; Us11 binds to PACT, RIG-I and MDA-5 to inhibit interaction with MAVS [58,59*], γ34.5 binds to TBK1 and inhibits IRF3 phosphorylation [60*], as does VP24 [61], Us3 hyper-phosphorylation of IRF3 blocks activation [62], ICP0 inhibits IRF3 translocation to the nucleus [63], and VP16 interferes with IRF3-CBP complex to inhibit transcription [15].…”
Section: Hsv Evasion Of Host Antiviral Responsesmentioning
confidence: 99%
“…Us3 interrupts TCR signaling by inhibiting the linker for activation of T cells (LAT) [53]. In T cells, HSV inhibits NF-κB activation and synthesis of pro-inflammatory cytokines like IL-2 and TNF-α, while activating STAT3 and the MAPK p38 and JNK pathways, and IL-10 synthesis [75].…”
Section: Hsv Evasion Of Host Antiviral Responsesmentioning
confidence: 99%
“…The earliest sign of immune exhaustion is a decrease in immune cells' capacity to secrete IFN-γ and IL-2 [8,22,23]. Yang et al showed that the Us3 protein, which is expressed by HHV-1, inhibits T-cell activation and other immune responses [24].…”
Section: Discussionmentioning
confidence: 99%